2017
DOI: 10.1093/milmed/usx034
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Combat-Related Thoracic Trauma – Review of Penetrating Trauma

Abstract: Combat-related thoracic trauma continues to be a significant contributor to the morbidity and mortality of those injured during OEF and OIF. This review of the imaging manifestations of penetrating thoracic injury during OEF and OIF focuses on key diagnostic findings for clinicians caring for combat casualties. The distinct injury pattern and atypical imaging manifestations of penetrating trauma are important to recognize early due to the acuity of this patient population and the influence of accurate diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
0
13
0
5
Order By: Relevance
“…The penetrating instrument and the force of impact differ greatly between firearm injuries and stabbings resulting in vast trauma energy variation. Extent of injury also depends on the affected tissue type (911).…”
Section: Introductionmentioning
confidence: 99%
“…The penetrating instrument and the force of impact differ greatly between firearm injuries and stabbings resulting in vast trauma energy variation. Extent of injury also depends on the affected tissue type (911).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to finding intraluminal filling defects or pseudo-aneurysms, CTA can also detect vessel disruption by showing extravasation of contrast distal to normal vessel location. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…(Stranch, Zarzaur and Savage, 2017) Other authors have found that no difference whatsoever on mortality among chambers (Asensio et al, 1998) GSW have worst prognosis and higher mortality rates than SW. This difference is mainly explained by the object and the force of impact, (Gunn et al, 2014;Durso, Caban and Munera, 2015;Lichtenberger et al, 2018) and the fact that bullets can affect multiple and deeper structures than sharp objects. Moreover, sharp objects often function as temporary hemostasis, preventing profuse bleeding on the site of injury until the surgical team can approach and correct the defect on a controlled environment.…”
Section: Prognosismentioning
confidence: 99%